Entre a história e o mito : Oliveira Lima e a construção de heróis nacionais monarquistas pela historiografia - Costa, Roger Renilto Diniz (2016)
This study aims to lecture about the historiography of Manuel de Oliveira Lima in view of the representation of the emperors of Brazil as national heroes during the First Republic. To this end, our emphasis is to analyze some books of the historian Oliveira Lima in which his historiographical discourse turns to the Brazilian imperial past highlighting the role of governments as heroic and praising them in epic way in his narrative. Methodologically we conceive the historiography as a discourse for the purpose of analyzing it in its historicity, that is, addressing context of production and its discursive articulation. The reflection by us developed is back to the question of the constitution of Brazilian nationality, recurrent literate in production of the late nineteenth century and early twentieth century. In the analysis, we established a dialogue with other historians who have dedicated themselves to researching the life path of Oliveira Lima, and on other aspects, their historiography. We analyzed five works of Oliveira Lima, specifically: Dom João VI no Brasil; Formação Histórica da Nacionalidade Brasileira; O Império Brasileiro (1821-1889); O Movimento da Independência (1821-1822) e Historia Diplomatica do Brazil: O Reconhecimento do Imperio